Sebuah pemikiran perlawanan Chudori terhadap cengkeraman kekuasaan dalam Laut Bercerita - Sahertian, Michael Kevin Bryan; Nurulhady, Eta Farmacelia; Suryadi, Muhammad; Laluna, Fadila Rana (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to prove the ideology of resistance of Leila Salikha Chudori towards oppressive force via Laut Bercerita. Literary work is a product of the author’s critical thinking; therefore, it is important to understand Chudori’s ideology in her work. From a Marxist point of view, there is a battle for domination in every society. This study tries to understand where is the ideological position of Chudori in the battle for domination. The method used to conduct this research is qualitative descriptive. Research on Laut Bercerita was a literature study that uses a Marxist approach. Theories that will be used are Antonio Gramsci's Theory of Hegemony and Louis Althusser's Theory of State Apparatus. The study concludes that Chudori is a figure of resistance in a battle for domination, which means Chudori's ideological position belongs to the group that refuses to be dominated.